PENGENDALIAN TATA RUANG DALAM PEMBANGUNAN DAN PERENCANAAN TATA KOTA - Ida Bagus Prastika; I Nyoman Wita (Kertha Negara : Journal Ilmu Hukum, 2014)
In the development or construction of a city would be based on planning, spatial planning is the first step in determining how the spatial patterns that would be implemented, the use of space control is an attempt to ensure the achievement of the goals and objectives of spatial plans. Spatial control guided by the directives set out in the regional spatial structure plans and land-use planning at the provincial and city levels. Control land use permitting is done also through the use of space, the provision of incentives and disincentives, as well as the imposition of sanctions. Permitting the use of space is intended as an effort to curb use of space so that any use of space must be made in accordance with the layout plan.